A Life Cycle Model of Female Labour Supply - Heckman, James J.; Macurdy, Thomas E. (Review of Economic Studies, 1980)
James J. Heckman, Thomas E. Macurdy; A Life Cycle Model of Female Labour Supply, The Review of Economic Studies, Volume 47, Issue 1, 1 January 1980, Pages 47–74